2013
DOI: 10.1039/c3fo60088b
|View full text |Cite
|
Sign up to set email alerts
|

Blood anticoagulation and antiplatelet activity of green tea (−)-epigallocatechin (EGC) in mice

Abstract: EGC was prepared from green tea polyphenols through column chromatography of a polyamide (3.6 × 40 cm). Three dosages of EGC (0.25, 0.5, 1.0 g kg(-1) d(-1)) were ingested respectively by ICR mice via gavage. Compared with the control group, group EGC0.5 (dosage, 0. 5 g kg(-1) d(-1)) and group EGC1.0 (dosage, 1.0 g kg(-1) d(-1)) presented significant inhibition on platelet aggregation in mice accompanied by 18.4 and 25.6% of inhibition ratio, respectively. The bleeding times (BT) of mice in group EGC0.5 and gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…Tea consumption has been shown to be useful for the prevention of many debilitating human diseases. Several published studies have reported similar results to those reported herein, showing that tea consumption can reduce CHD risk [1112]. In our study, we observed that tea consumption was associated with a reduced risk of CHD in female participants, but not in male participants, in Guangzhou, China.…”
Section: Discussionsupporting
confidence: 90%
“…Tea consumption has been shown to be useful for the prevention of many debilitating human diseases. Several published studies have reported similar results to those reported herein, showing that tea consumption can reduce CHD risk [1112]. In our study, we observed that tea consumption was associated with a reduced risk of CHD in female participants, but not in male participants, in Guangzhou, China.…”
Section: Discussionsupporting
confidence: 90%
“…98,99 Regarding quantitative or qualitative platelet changes and hemostasis (bleeding risk), only few information is available, limited to animal studies. Indications on an increased tail bleeding time were made for animals treated with diallyl trisulfides, 121 curcumin, 40,122 epigallocatechin, 123 nobiletin, 124 or chlorogenic acid. 51 Few other papers indicated that phytochemicals can inhibit thrombus formation and platelet function without increased tail bleeding times, i.e., for quercetin, 125 myricetin, 72 and delphinidin glucoside.…”
Section: Implications For Thrombosis and Hemostasismentioning
confidence: 99%
“…Aglycones act as competitive thrombin inhibitors, while chokeberry extract significantly inhibits thrombin amidolytic activity. (b) FXa inhibition [63][64][65]. Flavonoids: procyanidin B2, cyanidin, quercetin, and silybin bind S1-S4 pockets in vicinity of the FXa active site and block access of substrates to Ser195, thereby directly inhibiting FXa amidolytic activity.…”
Section: Ampk-independent Mechanismsmentioning
confidence: 99%